Notes (accompanied by Plans and Sketches) regarding the 'Picts House' or Underground Chamber at Tealing, Forfarshire (Proceedings of the Society of Antiquaries of Scotland, 1873)
[The journal notes that this paper will be printed in a later part of the Proceedings.]